Family Communication Patterns of Abuser and Victim in Sexual Abuse Case Resolutions towards Children in Medan City Resort Police - Haslinda Haslinda; Lahmuddin Lubis; Syukur Kholil (Budapest International Research and Critics University, 2019)
This study aims to analyze the family communication patterns of abuser and victim in sexual abuse case resolutions towards children, the application of the principles of Islamic communication in resolving sexual abuse cases towards children and to know the obstacles in solving sexual abuse cases for underage children in the law area of Medan City Resort Police. The research method used in this study is a descriptive qualitative approach. This method describes the current state of the subject or object of study based on facts that appear or as they are. The results of the study shows that the family communication patterns of abuser and victim in sexual abuse case resolutions towards children in Medan City Resort Police are the Equality Pattern, Balance Split Pattern, Unbalanced Split Pattern and Monopoly Patterns.